Design and experimental study on pneumatic extruding direct-writing deposition for multi-materials. (September 2018) - Ma, Ming; Chen, Peng; Zhao, Lifei; Zhang, Honghai
Abstract: To develop a low-cost direct-writing-based additive manufacturing for multi-materials, a concept design of pneumatic extruding direct-writing deposition (PEDWD) was presented in this paper. Sn63Pb37 alloy and YH-W906 paraffin wax were used as raw materials in this study, they were heated to be molten in the chambers. Under the driving of compressed nitrogen, the molten materials were squeezed out from the nozzle and formed parts on an aluminium alloy substrate. By conducting the experiments and measuring the shape of deposited two-dimensional (2D) and three-dimensional (3D) parts, the influence induced by the structure design of nozzle and driving pressure on the mass flow rate of molten material was analysed both theoretically and experimentally. The stability and reliability of PEDWD were proved by the final successful fabrication of 2D and 3D parts. This paper shows that PEDWD provides a novel way to fabricate parts for multi-materials with low-cost and flexibility.